The multistage homotopy perturbation method for solving chaotic and hyperchaotic Lu system - Chowdhury, M. S. H.; Razali, Nur Isnida; Asrar, Waqar; Rahman, M. M. (Hindawi Publishing Corporation, 2015)
The multistage homotopy-perturbation method (MHPM) is applied to the nonlinear chaotic and hyperchaotic Lü systems. MHPM is a technique adapted from the standard homotopy-perturbation method (HPM) where the HPM is treated as an algorithm in a sequence of time intervals. To ensure the precision of the technique applied in this work, the results are compared with a fourth-order Runge-Kutta method and the standard HPM. The results show that the MHPM is an efficient and powerful technique in solving both chaotic and hyperchaotic systems.